2022
DOI: 10.18502/ijrm.v20i11.12357
|View full text |Cite
|
Sign up to set email alerts
|

Risk of endometrial, ovarian, and breast cancers in women with polycystic ovary syndrome: A systematic review and meta-analysis

Abstract: Background: Although several studies have evaluated the risk of gynecological cancers in women with polycystic ovary syndrome (PCOS), there are controversies regarding it. Objective: This study aimed to investigate the association of PCOS with endometrial, ovarian, and breast cancers. Materials and Methods: PubMed, Scopus, Web of Science, and Google Scholar databases based on MESH terms using the combination of the appropriate keywords were searched to retrieve observational studies on endometrial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“… 6 , 32 The prevalence of endometrial cancer has been reported to be increased 3-5 fold in those with PCOS in the postmenopause years, and an increased risk for ovarian cancer has been reported in younger women with PCOS in the premenopause years. 6 , 123 , 124 , 125 In our cohort, we have shown that all malignancy was increased by 30% in those with PCOS, suggesting that increased awareness and screening may be warranted.…”
Section: Discussionmentioning
confidence: 73%
“… 6 , 32 The prevalence of endometrial cancer has been reported to be increased 3-5 fold in those with PCOS in the postmenopause years, and an increased risk for ovarian cancer has been reported in younger women with PCOS in the premenopause years. 6 , 123 , 124 , 125 In our cohort, we have shown that all malignancy was increased by 30% in those with PCOS, suggesting that increased awareness and screening may be warranted.…”
Section: Discussionmentioning
confidence: 73%
“…Some studies have considered the risk of ovarian and breast cancer in PCOS patients to be considerable, and some have not observed a significant relationship (11,32). Other studies have shown that the risk of uterine and breast cancer was higher in people with PCOS (10)(11)(12). In several systematic reviews, it was found that endometriosis is related to PCOS.…”
Section: Risk Of Ovarian and Breast Cancer In Pcosmentioning
confidence: 99%
“…There are conflicting results regarding the relationship between PCOS and breast cancer. Some studies have reported an association, but others have not (9,10). The actual risk remains unclear; Because their results are often contradictory and the risk of developing these cancers in women with PCOS is still debated (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Although some reproductive and metabolic risk factors for breast cancer, such as low parity and obesity, are also characteristics of PCOS, knowledge regarding the association between PCOS and breast cancer is less conclusive and has only been investigated in ve cohort- [13][14][15][16][17] and three case-control studies [18][19][20]. Most of the previous studies are included in two recent meta-analyses [21,22], both of which reported null associations (OR: 0.94, 95% CI: 0.78-1.14 and OR: 1.1, 95% CI: 0.87-1.4, respectively). The two meta-analyses encompass slightly different studies, and most of the studies have notable limitations including inadequate information on PCOS de nitions, small sample size and short follow-up and insu cient confounder adjustment.…”
Section: Introductionmentioning
confidence: 99%